Historical and Geographic Factors of Institutional Quality: An Empirical Analysis - Babar, Zaheer Ahmed; Dr. Muhammad Abdul Quddus; Dr. Majid Ali (Journal of Peace, Development and Communication, 2021)
This paper contributes to the debate about historical and geographic factors of institutional quality. It used non economic factors which caused institutional quality better or worse. These non economic factors are geographic location, colonial background, fractionalization in religion, language and ethnic, legal system and abundant of natural resources. This study took 68 countries all around the world which have developed and developing countries and apply simple OLS and 2SLS technique to explore the determinants factors. The study decomposed institutional quality into economic, legal and political institutions. Fractionalization with level of development and under the colonial background has negative affected the institutional quality. Colonization has negative impact on Institutional Quality but under the level of development, colonization has insignificant impact on Institutional quality. In this study without level of development natural resources has negative impact but under the level of development it has insignificant impact on institutional quality except economic institutions. Without level of development, Geographic location is a significant impact on all three kind of Institutions in this study but under the level of development, it has insignificant impact.